Korelasi Efikasi Diri dengan Tingkat Intradialitic Weight Gain (IDWG) Pada Pasien Gagal Ginjal Kronik - Purwandari, Nila Putri; Ahmad, Aldam Fajar; Faidah, Noor; Putri, Devi Setya (Poltekkes Kemenkes Aceh, 2024)
Background: Kidney failure in carrying out its functions at the terminal stage requires treatment in the form of hemodialysis. In hemodialysis patients, adhering to fluid intake restrictions has a very vital role to prevent further complications. The success of fluid and diet management in therapy is measured by the level of Interdialytic Weight Gain (IDWG). One of the things that affects IDWG during the hemodialysis therapy period is self-efficacy. Purpose: To determine the relationship of self-efficacy with the level of Interdialytic Weight Gain (IDWG) of chronic kidney disease patients in the hemodialysis unit of RAA Soewondo Pati Hospital. Methods: This study is a correlational analytical study, with a cross-sectional research design, a sampling method using consecutive sampling, with a total sample of 68 respondents and data collection using questionnaires. Results: The results of this study found that respondents with high category self-efficacy and IDWG levels in the mild category were 38 respondents (50.5%), the results of the analysis with the spearman rank correlation test obtained p value = 0.000< α (0.05) which can be concluded to be a relationship between self- efficacy and the interdialytic weight gain (IDWG) level of chronic kidney disease patients in the hemodialysis unit of RAA Soewondo Pati Hospital. Conclusion: There was a significant relationship between self-efficacy and interdialytic weight gain (IDWG) levels of chronic kidney disease patients in the hemodialysis unit of RAA Soewondo Pati Hospital.